2020
DOI: 10.3390/tropicalmed5030108
|View full text |Cite
|
Sign up to set email alerts
|

A Serological Survey of Selected Papua New Guinea Blood Donors for Hepatitis B and Related Co-Infections

Abstract: Hepatitis B virus (HBV) infection is a serious problem and earlier studies in Papua New Guinea have reported a high prevalence of hepatitis B virus infection. These studies were undertaken using insensitive tests and before an expanded immunization program. The current HBV status is therefore uncertain. A retrospective study to investigate the HBV status was carried out using blood donor data at Nonga General Hospital, East New Britain Province, Papua New Guinea, from January 2003 to December 2018. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…In this review, viraemic prevalence of HCV infection among the general population was ≤1% in most WHO WPR countries where data were identified (Australia, China, Japan, Malaysia, Republic of Korea, Singapore, Viet Nam, and Hong Kong SAR). While HCV antibody prevalence was comparatively high in Papua New Guinea at 4.2%, only one small study among blood donors (n = 1206) was identified [ 10 ] and this estimate may not be representative of the general population. HCV antibody prevalence was also comparatively high at 3.9% in Cambodia where, similarly, only one small study (n = 868) was identified [ 11 ], However, hepatitis C viraemic prevalence in this setting was substantially lower at 1.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, viraemic prevalence of HCV infection among the general population was ≤1% in most WHO WPR countries where data were identified (Australia, China, Japan, Malaysia, Republic of Korea, Singapore, Viet Nam, and Hong Kong SAR). While HCV antibody prevalence was comparatively high in Papua New Guinea at 4.2%, only one small study among blood donors (n = 1206) was identified [ 10 ] and this estimate may not be representative of the general population. HCV antibody prevalence was also comparatively high at 3.9% in Cambodia where, similarly, only one small study (n = 868) was identified [ 11 ], However, hepatitis C viraemic prevalence in this setting was substantially lower at 1.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [ 10 , 11 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , …”
Section: Table A1unclassified